The Financial Impact of Eliminating a NCAA Division I Men’s Sport on the Athletic Budget: Is Title IX to Blame? - Marx, Anne; Cormier, Joel; Ciapalo, Roman (Journal of Intercollegiate Sport, 2023)
The purpose of this study was to examine changes to the budgets of women’s athletics, men’s basketball, and football when an NCAA Division I intercollegiate men’s team was eliminated.  Stakeholder theory provided the theoretical framework for the study.  Central to the research was the relationship between the elimination of men’s teams and Title IX.  Title IX of the Educational Amendments of 1972 is the landmark legislation passed to provide equal educational opportunities for women, including athletics.  Eighty-five institutions were included in the study.  Data were obtained from the Equity in Athletics Disclosure Act (EADA) for the four years before and after the elimination of a men’s sport between 2007 and 2014, resulting in 15 years of budgetary data. Comparisons of budgets were conducted between the four years prior to when a men’s sport had been cut and the four years after the sport had been eliminated. Analyses indicated that when a men’s sport program had been eliminated, the budget resources of the eliminated program were reallocated primarily to the budgets of men’s basketball and football rather than to the women’s athletics budget. The argument of athletic administrators that decisions to cut programs were based on the need to comply with Title IX was not supported by the data and belied the prevailing view that men’s sports were cut to fund women’s sports in order to comply with Title IX.